Ranitidine‐induced anaphylaxis: clinical features, cross‐reactivity, and skin testing. Issue 4 (April 2016) - Park, K. H.; Pai, J.; Song, D.‐G.; Sim, D. W.; Park, H. J.; Lee, J.‐H.; Jeong, K. Y.; Pan, C.‐H.; Shin, I.; Park, J.‐W.
Summary: Background: Histamine H2 receptor antagonists are commonly prescribed medications and are known to be well tolerated. However, 99 cases of ranitidine‐induced anaphylaxis occurred in Korea from 2007 to 2014. Objective: The purpose of this study was to determine the incidence, clinical features, and diagnostic methods for ranitidine‐induced anaphylaxis. Methods: Ranitidine‐related pharmacovigilance data from 2007 to 2014 were reviewed. Adverse drug reactions with causal relationships were selected, and clinical manifestations, outcomes, and drug‐related information were assessed. For further investigation, 8 years of pharmacovigilance data were collected at a single centre. Twenty‐three patients participated in in vivo and in vitro studies. Skin tests, oral provocation tests, and laboratory tests were performed, including tests using other kinds of histamine H2 receptor antagonists. Results: Over 7 years, 584 patients suffered adverse reactions to ranitidine. The most common manifestation was cutaneous symptoms. Among them, 99 patients (17.0%) experienced anaphylaxis. In a single‐centre study, skin prick tests were positive in 91.7% of ranitidine‐induced anaphylaxis patients (11/12); the optimal concentration was 20 mg/mL. Detection of ranitidine‐specific immunoglobulin E failed. Cimetidine and proton pump inhibitors showed no cross‐reactivity with ranitidine based on the skin prick test, oral provocation test, or clinical determination. Surprisingly, 82.6% of patients reintroduced ranitidine and re‐experienced the same adverse reactions because ranitidine was not considered the culprit drug. Conclusions and Clinical Relevance: Although ranitidine is known as a safe drug, it can also cause diverse adverse reactions, including anaphylaxis. This study demonstrates the need to pay attention to adverse reactions to ranitidine and consider ranitidine as a cause of anaphylaxis.